2002
DOI: 10.2169/internalmedicine.41.667
|View full text |Cite
|
Sign up to set email alerts
|

Afebrile Scrub Typhus (Tsutsugamushi disease) with Acute Respiratory Distress Syndrome.

Abstract: A 74-year-old Japanese man with scrub typhus presented without the typical symptomof high fever and subsequently developed the complication of acute respiratory distress syndrome. It was suspected that exposure occurred at the river side of Kinugawa, Tochigi Prefecture, Japan. His body temperature was below 38.0°C. After intensive supportive care and minocycline therapy, he dramatically recovered. With the increase in popularity of outdoor recreation, scrub typhus can be found in clinics all over Japan. Physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Previous studies have reported an incidence of 11-29%. [791217] for acute respiratory distress syndrome (ARDS) in patients admitted for scrub typhus. In our study, 85 patients (73.3%) fulfilled criteria for the diagnosis of ARDS, the higher incidence probably a reflection of the inclusion of only the sicker ICU patients in the cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported an incidence of 11-29%. [791217] for acute respiratory distress syndrome (ARDS) in patients admitted for scrub typhus. In our study, 85 patients (73.3%) fulfilled criteria for the diagnosis of ARDS, the higher incidence probably a reflection of the inclusion of only the sicker ICU patients in the cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[123456789101112131415] Once a dreaded disease in the pre-antibiotic era, reports suggest that scrub typhus continues to be a public health problem in South Asian and Western Pacific regions. [14161718192021] More recent publications have highlighted that scrub typhus is an important cause of acute undifferentiated febrile illness in India[18] leading to organ dysfunction and death in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…The early diagnosis of Tsutsugamushi disease is considered difficult because of lack of specific clinical findings (1,11). Wide-spectrum β-lactam antibiotics may be tried in vain, for a 'fever of unknown origin'.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic assays (including an indirect immunoperoxidase test and an immunofluorescence assay) are the mainstays of a laboratory diagnosis (1,10). However, the clinical findings are non-specific (1,11), and the manifestations of the disease range widely from mild and self-limiting to fatal (10). Several severe complications may occur, such as respiratory complications (1, 11) acute renal failure (12,13) and coagulation disorders (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation